2016
DOI: 10.1021/acs.jpcc.6b01555
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observations of Phase Transitions in Metastable Nickel (Carbide)/Carbon Nanocomposites

Abstract: Nanocomposite thin films comprised of metastable metal carbides in a carbon matrix have a wide variety of applications ranging from hard coatings to magnetics and energy storage and conversion. While their deposition using nonequilibrium techniques is established, the understanding of the dynamic evolution of such metastable nanocomposites under thermal equilibrium conditions at elevated temperatures during processing and during device operation remains limited. Here, we investigate sputter-deposited nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 114 publications
6
66
0
2
Order By: Relevance
“…A meta-study on this subject can be found in reference 4. A recent study 6 confirmed, that Ni 3 C in such films only decomposes at temperatures well above 250 • C.…”
Section: Introductionmentioning
confidence: 75%
“…A meta-study on this subject can be found in reference 4. A recent study 6 confirmed, that Ni 3 C in such films only decomposes at temperatures well above 250 • C.…”
Section: Introductionmentioning
confidence: 75%
“…Possible degradation scenarios include exposure to visible light radiation or heating to elevated temperatures in ambient atmosphere [30]. In order to study the stability of our PVD MoS 2 films, we employed in situ laser annealing [3940] in ambient air coupled with Raman spectroscopic investigations (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…In between are metals like Ni, Co, and Fe with a low affinity to carbon. These metals are still able to interact with carbon but the reaction products depend on many parameters like, for example, the deposition technique, substrate temperature, and metal content (Bayer et al, 2016). For instance, nickel is a prominent catalyst in the production of carbon nanotubes and graphene (Garlow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%